You are on page 1of 10

ECE/CpE 307S ADVANCED ENGG MATH for ECE/CpE

COLLEGE OF ENGINEERING
COLEGIO SAN AGUSTIN

Topic: Laplace Transform


Prepared by: Engr. Vicente Y. Buenconsejo, Jr., PECE, MT
Pierre Simon Marquis De Laplace (1749-1827), great French mathematician develop the
theory of potential and contributions to celestial mechanics, astronomy in general, special
functions, and probability theory. Napoleon Bonaparte was his student for a year.
3 Main Steps
1. The given hard problem is transformed into a simple equation called subsidiary equation.
2. The subsidiary equation is solved by purely algebraic manipulations.
3. The solution of the subsidiary equation is transformed back to obtain the solution of the
given problem.
These process is made easier by tables of functions and their transforms, whose role
is similar to that of integral tables of calculus. The switching from operations of calculus to
algebraic operations on transforms is called OPERATIONAL CALCULUS. For engineers,
Laplace transform method is practically the most important operational method.
Let f (t ) = given function defined for all t 0.
Multiply f (t ) by e st and integrate with respect to t from 0 to . We have;

F ( s ) = e st f (t )dt
0

where:
F (s ) = Laplace transform of the original function and will be denoted by L(f).
f (t ) = original function

(1)

F (s ) = L(f) =

e st f (t )dt

Remember that:
f depends on t
F depends on s
The original function f (t ) in (1) is called the inverse transform or inverse of F ( s ) and will be
denoted by L1 (F).
f (t ) = L1 (F)
Notation:
Original functions are denoted by lowercase letters
Transforms by the same letters in CAPITALS
So that:
F ( s ) denotes the transform of f (t )
Y ( s ) denotes the transform of y (t )
Example 1.
f (t ) = 1 when t 0. Find F ( s ) .
From (1) by integration:

F ( s ) = L(f) =

e st f (t )dt
e st dt

1 st
e ( s )dt
s 0

1
= e st [0
s
1 s ()
e s (0) }
= {e
s
1
= {0 1}
s
1
F (s ) = L(1) =
ans.
s

Example 2. Laplace Transform of the exponential function.


f (t ) = e a when t 0. Find F (s ) where a is constant.
Solution:
F (s ) = L(f) =

F (s ) = L( e at ) =

e st f (t )dt

e st e at dt =

e st + at dt =

e ( s a )t dt

1 ( s a )t
e
()( s a )dt
s a 0
1
1
=
[e ( s a ) t ]0 =
[e ( s a ) e ( s a ) 0 ]0
sa
sa
1
[0 1]
=
sa
1
F (s ) = L( e at ) =
ans.
sa

THEOREM 1: Linearity of the transform


L{af (t ) + bg (t )} = aL{ f (t )} + bL{g (t )}
PROOF: By definition;

L{af (t ) + bg (t )} = e st [af (t ) + b{g (t )]dt


0

L{af (t ) + bg (t )} = a e st f (t )dt + b e st g (t )dt


L{af (t ) + bg (t )} = aL{ f (t )} + bL{g (t )}
Application of theorem 1:
Example 3:
1
f (t ) = (e at + e at ) . Find F (s ) .
2
Solution:
1
1
1
L{ (e at + e at )} = L(e at ) + L(e at )
2
2
2
1 1
1 1
= (
)
)+ (
2 sa
2 s+a
1 1
1
= (
+
)
2 sa s+a
1 s+a+sa
= [
]
2 ( s a )( s + a )
1
2s
= [ 2
]
2 (s a 2 )
1
s
L{ (e at + e at )} = 2
ans.
2
s a2

Using the table:

Example 4:
f (t ) = a + bt + ct 2 a, b, c = cons tan ts . Find F (s ) .
Solution:
L(a + bt + ct 2 ) = aL(1) + bL(t ) + cL(t 2 )
1
1
2!
= a ( ) + b( 2 ) + c ( 3 )
s
s
s
a b 2!c
= + 2+ 3
ans.
s s
s
Example 5:
f (t ) = e a bt . Find F (s ) .
Solution:
L(e a bt ) = L(e a e bt ) = e a L(e bt )
1
= ea (
)
s+b
ea
=
s+b

ans.

Practice Problems:

1. Find the Laplace transforms of the following functions. Show the details of your work.
a. t2 - 2t
b. (t2 3)2
c. cos 2t
d. sin 4t
e. e3a-2bt

TRANSFORMS OF DERIVATIVES:
Laplace transforms replaces operations of calculus by operations of algebra on
transforms.
The differentiation of f (t ) is replaced by multiplication of L(s ) by s .
(1)

L( f ' ) = sL( f ) f (0)

; f (t ) is continuous for all t 0

where:
L( f ' ) = Laplace transform of the first derivative of f (t )
L( f ) = Laplace transform of f (t ) ; also F (s )
f (0) = value of the function at time t = 0

And:
L( f '' ) = sL( f ' ) f ' (0)

; substitute L( f ' ) in (1)

L( f '' ) = s[ sL( f ) f (0)] f ' (0)


L( f '' ) = s 2 L( f ) sf (0) f ' (0)

Similarly;
L( f ''' ) = s 3 L( f ) s 2 f (0) sf ' (0) f '' (0)

Or in general;
L( f n ) = s n L( f ) s n 1 f (0) s n 2 f ' (0) f n 1 (0)

Example 1:
f (t )

= t 2 . Derive L( f ) .

Solution:
1. Take the derivatives
f (t ) = t 2

f ' ( t ) = 2t

f '' ( t ) = 2

f ( 0) = 0 2

f ' (0) = 2(0)

f '' (0) = 2

f (0) = 0

f ' ( 0) = 0

2. Take the Laplace of the highest derivative of f (t ) .


L( f '' ) = L( 2) = 2 L(1)

3. Substitute to equation of differentiation of the highest derivative


L( f '' ) = s 2 L( f ) sf (0)] f ' (0)
L( 2) = s 2 L( f ) s(0)] (0)

From the table L( 2) =

2
s

2
= s 2 L( f )
s
L( f ) =

2
s3

ans. (see table)

Note: Different Process but same answer!!!

Example 2:
Derive the Laplace transform of cos wt .
Solution:
1. Differentiate f (t )
f ( t ) = cos wt

f ' ( t ) = w sin wt

f '' ( t ) = w 2 cos wt

f (0) = cos w (0)

f ' (0) = w sin w (0)

f '' (0) = w 2 cos w (0)

f ( 0) = 1

f ' ( 0) = 0

f '' (0) = w 2

2. Take the Laplace of the highest derivative of f (t ) .


L( f '' ) = L( w 2 cos wt )

But: f (t ) = cos wt

w 2 = constant

L( f '' ) = w 2 L(cos wt ) = w 2 L( f )

3. Substitute to equation of differentiation of the highest derivative


L( f '' ) = s 2 L( f ) sf (0) f ' (0)
w 2 L( f ) = s 2 L( f ) s(1) (0)
s = s 2 L( f ) + w 2 L( f )
L( f ) =

s
s + w2
2

L(cos wt ) =

s
s + w2
2

ans. (see table)

Assignment:
1. Derive L(sin wt ) using transforms of derivative.
2. f ( t ) = sin 2 t

INITIAL VALUE PROBLEMS:


Given the Differential Equation:
(5)

y '' + ay ' + by = r (t )

where:
a & b = constants
r (t ) = input (driving force) applied to the mechanical system
y (t ) = output (response of the system)

1st Step: Transform (5) by means of (1) and (2) writing Y = L( y ) & R = L(r )

y '' + ay ' + by = r (t )
[ s 2Y sy (0)] y ' (0)] + a[ sY y (0)] + bY = R

this is the subsidiary equation

Collecting Y terms we have;

s 2Y sy (0) y ' (0) + asY ay (0) + bY = R


( s 2 + as + b)Y = ( s + a) y (0) + y ' (0) + R
2nd Step: Solve the subsidiary equation algebraically for Y. Multiply the subsidiary equation by:
(6)

1
= Q(Transfer _ function)
coeff of Y
1
= [( s + a ) y (0) + y ' (0) + R]Q
( s + as + b)
Y = [( s + a ) y (0) + y ' (0)]Q + RQ

[( s 2 + as + b)Y ]

(7)

If y (0) = y ' (0) = 0


Y = RQ
Y L( output
Q= =
)
R L( input )

Note that Q depends only on a & b, neither on r(t) or initial condition.


3rd Step: Reduce (7) usually by partial fraction, to a sum of terms whose inverse can be found
from the table so that;
y (t ) = L1 (Y ) of (5) is obtained.
Example 1:
Solve: y" y = t

y ( 0) = 1

y ' ( 0) = 1

Solution:
1. From the table and (2) get the subsidiary equation
y" y = t
s 2Y sy( 0 ) y' ( 0 ) Y =

1
s2

1
s2
1
( s 2 1)Y = s + 1 + 2
s

s 2Y s (1) (1) Y =

2. The transfer function is Q =

1
and (7) becomes;
s 1
2

1
Q
s2
s +1
1
Y = 2
+ 2 2
s 1 s ( s 1)
s +1
1
1
Y =
+[ 2
2]
( s 1)( s + 1) ( s 1) s
Y = ( s + 1)Q +

Y =

1
1
1
+ 2
2
( s 1) ( s 1) s

3. From this expression, find y (t ) from table.


y (t ) = L1 (Y ) = L1{

1
1
1
} + L1{ 2
} L1{ 2 }
( s 1)
( s 1)
s

y (t ) = et + sinh t t

ans.

Diagram:

Given Problem

Subsidiary Equation

y" y ' = t
y ( 0) = 1
y ' ( 0) = 1

( s 2 1)Y = s + 1 +

t space

1
s2

s space

Solution of the Given


Problem

Solution of Subsidiary
Equation

y (t ) = et + sinh t t

Y =

t space

1
1
1
+ 2
2
( s 1) ( s 1) s
s space

Practice Problems:
1. y"+2 y '+ y = e t
2. y '+3 y = 10 sin t
3. y '+0.2 y = 0.01t
4. y" y '2 y = 0

y (0) = 1
y ( 0) = 0
y (0) = 0.25
y ( 0) = 8

y ' ( 0) = 1

y ' ( 0) = 7

LAPLACE TRANSFORM OF THE INTEGRAL OF A FUNCTION


Theorem:
Integration of a function corresponds to division of its transform by s
F (s)
s
Or if we take the inverse transform
t
1 F ( s )
0 f ( )d = L { s }
where:
t

L{ f ( )d } =
0

f (t ) = f ( )d
0

Example:
L( f ) =

Solution:

1
s ( s + w2 )
2

Find f (t ).

s>0

From the table we have:


L1 (

1
1
) = sin wt
2
s +w
w
2

Note that:
f (t ) =

F ( s)
}
s
1
= L1{ 2
}
s ( s + w2 )

f ( )d = L1{

From this and Theorem 3 we have:


F ( s)
}
0
s
t
1
= f ( )d = L1{ 2
}
0
s ( s + w2 )

f (t ) =

f ( )d = L1{

Note from table:


1
1
) = sin wt
2
s +w
w
Then;
L1 (

( w sin w )d
0

=
=
=
=
f (t ) =

1 t
sin wd
w 0
1 1 t
[
sin w ( w)d ]
w w 0
1
[ cos w ]t0
w2
1
[ cos wt ( cos w(0))]
w2
1
[1 cos wt ]
ans.
w2

Example 2: Derive the formula 20 in table using the transform of Integrals


L( f ) =

1
s ( s + w2 )
2

Find f (t ).

Solution:
f (t )

f ( )d = L1{

1
}
s ( s + w2 )
2

From the table we have:


L1 (

1
1
) = 2 [1 cos wt ]
2
s( s + w )
w
2

=[
0

1
(1 cos w )]d
w2

=
=
=
=
f (t ) =

Practice Problems:
1
1. L1 ( 5
)
s + s3
1
2. L1 ( 3
)
s s

1 t
(1 cos w )d
w2 0
1
sin w t
[
]0
2
w
w
1
sin wt sin w(0)
{[t 0] [

]}
2
w
w
w
1
sin wt
[t
]
2
w
w
1
[ wt sin wt ]
ans.
w3